LEXICAL-SEMANTIC PROPERTIES OF HEMATOLOGICAL TERMS IN MEDICINE - Ergashova Iroda (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: In the field of Medicine, hematological Terms form an interesting and complex material for studying the lexical-semantic edges of linguistics. Hematology is the field of medicine that studies blood and its composition, blood diseases, their diagnosis and treatment, and the terminology in this area has clear, systematic and specific lexical-semantic properties. Lexical-semantic analysis of hematological terms on the example of English and Uzbek languages shows the integration of language and medical science, and also allows you to identify terminological connections and differences between the two languages.